Helmes-Hayes/Santoro (eds.): Everett Hughes - Egger de Campo, Marianne (Serendipities. Journal for the Sociology and History of the Social Sciences, 2017)
Book review of: Helmes-Hayes, Richard C., and Marco Santoro (eds.) (2016) The Anthem companion to Everett Hughes, London, New York: Anthem Press. 243 pp. ISBN: 978-0-85728-178-4. Price: $ 115 / £ 70 (Hardcover)